Answer with explanation:
The given differential equation is
x²y" -7 x y' +1 6 y=0---------(1)
Let, y'=z
y"=z'
![(dy)/(dx)=z\\\\y=zx](https://img.qammunity.org/2020/formulas/mathematics/college/ifuswu4a8mgyssi8l2js7aysckovkyy3el.png)
Substitution the value of y, y' and y" in equation (1)
→x²z' -7 x z+16 zx=0
→x² z' + 9 zx=0
→x (x z'+9 z)=0
→x=0 ∧ x z'+9 z=0
![x (dz)/(dx)+9 z=0\\\\(dz)/(z)=-9 (dx)/(x)\\\\ \text{Integrating both sides}\\\\ \log z=-9 \log x+\log K\\\\ \log z+\log x^9=\log K\\\\\log zx^9=\log K\\\\K=zx^9\\\\K=y'x^9\\\\K x^(-9)d x=dy\\\\\text{Integrating both sides}\\\\y=(-K)/(8x^8)+m](https://img.qammunity.org/2020/formulas/mathematics/college/hpvaigmeif9surq11hrbl5oxjlt89c9ycn.png)
is another independent solution.where m and K are constant of integration.